2019
DOI: 10.17219/acem/91826
|View full text |Cite
|
Sign up to set email alerts
|

IL-4-polarized BV2 microglia cells promote angiogenesis by secreting exosomes

Abstract: Background. The microglia cell transfer has been shown to play a protective role in ischemic stroke. Microglia cells may play this nerve-protective role via the promotion of angiogenesis. However, the underlying mechanisms are largely unknown and need further investigation. Objectives. The aim of this study was to investigate the pro-angiogenesis effects of unpolarized, interleukin 4 (IL-4)-polarized or lipopolysaccharide (LPS)-polarized BV2 microglia cells both in vivo and in vitro. We also investigated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 35 publications
1
71
0
Order By: Relevance
“…In the present study, TWS119 facilitated post-stroke angiogenesis in the ischemic brain, but failed to directly promote angiogenesis in OGD endothelial cells. Evidence revealed that microglia in anti-inflammatory phenotype promote angiogenesis [39]. Using a conditioned medium transfer system, we found that TWS119 promoted angiogenesis of OGD endothelial cells via anti-inflammatory phenotype microglia-mediated amelioration of inflammatory microenvironment, suggesting a proangiogenic effect of TWS119 in anti-inflammatory phenotype polarization-dependent manner.…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, TWS119 facilitated post-stroke angiogenesis in the ischemic brain, but failed to directly promote angiogenesis in OGD endothelial cells. Evidence revealed that microglia in anti-inflammatory phenotype promote angiogenesis [39]. Using a conditioned medium transfer system, we found that TWS119 promoted angiogenesis of OGD endothelial cells via anti-inflammatory phenotype microglia-mediated amelioration of inflammatory microenvironment, suggesting a proangiogenic effect of TWS119 in anti-inflammatory phenotype polarization-dependent manner.…”
Section: Discussionmentioning
confidence: 77%
“…There is evidence of crosstalk between microglia and endothelial cells. Polarization of microglia induced by IL-4 increased miR-26a in microglia-generated exosomes, which may promote tube formation in vitro and angiogenesis in vivo after ischemia [62]. Thus, exosomes exerted direct and indirect effects for repairing and regenerating brains after stroke.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand M2 microglia-derived exosomes containing miR-124 were shown to be absorbed by neurons and further boost neuronal survival by targeting the ubiquitinspecific protease 14 (Song et al, 2019). In addition, IL-4stimulated microglia was suggested to promote angiogenesis by secreting exosomes containing miR-26a, thereby reducing the damage caused by ischemic stroke (Tian et al, 2019). These studies indicate that M2 microglia play a protective role against ischemic stroke through miRNA-mediated regulation.…”
Section: Mirnas Associated With M2 Microgliamentioning
confidence: 90%